GOTHIC HAUNTING IN VALERII SHEVCHUK'S TALE THE BIRDS FROM THE INVISIBLE ISLAND - Maria Burdastykh (European Scientific Journal, ESJ, 2014)
Valerii Shevchuk, a prominent Ukrainian writer, has frequently employed the dark imagery in his work since the 1970s in order to disclose the perverseness of human mind, the dark side of contemporary society, and the horrors of the colonial Ukrainian past. This paper focuses on the Gothic conventions in his tale The Birds from the Invisible Island [Ptakhy z nevydymoho ostrova]. By analyzing the motifs and tropes of the ghost, the spectral, the double, the haunted house (castle), and the uncanny, we show that the writer creates a hybrid narrative that comprises the elements of the Gothic, the fantastic, the historical tale and the Utopia. This paper explicates that Shevchuk utilized the Gothic conventions in order to investigate the experience of servitude and its influence on human mind as well as the history of national oppression and struggle with national identity. Shevchuk transforms the trope of the haunted house into the claustrophobic space of a mysterious castle that establishes a broader discourse of the empire in his tale. The settings of the castle resemble the reality of a totalitarian state, for example the total control of thoughts and actions, denial of national history and the past, hostility to surrounding world, pervasiveness of terror and paranoia, physical tortures and violent punishments. The tale shows that the imperial 'other' disrupts the national identity and reduces the self to the specter.